HUBUNGAN ANTARA MINAT BELAJAR DAN HASIL BELAJAR GEOGRAFI SISWA DI SMA ADVENT BITUNG - Simbolon, Ester; Poli, Ellen Eva; Lobja, Xaverius Erick; Nismawati; Felix Rimba; Rahmad Hidayat (Fakultas Ilmu Sosial dan Hukum, 2025)
This study analyzes the relationship between learning interest and geography learning outcomes of students at SMA Advent Bitung using a quantitative survey method on 21 students. Data were collected through a questionnaire that measures learning interest based on indicators such as feelings of pleasure, attention, interest, engagement, and participation, and learning outcomes are measured through students' geography learning outcomes. The results show that students' learning interest is in the high category with an average score above 72, while the average geography learning outcome score is 73. Data analysis using the Pearson correlation test produced a correlation coefficient of 0.866, indicating a very strong relationship between the two variables. The t-test also showed significance below 0.05, confirming a significant positive relationship. This study concludes that increasing students' learning interest can be an effective strategy to improve their learning outcomes.